REVISITING INDIAN FOLK ART NAUTANKI FROM TRADITION TO CONTEMPORARY EXPRESSION: AN EMPIRICAL ANALYSIS - Tiwari, Jay Prakash; Verma, Adish Kumar; Joshi, Kulin Kumar; Prasad, Bishal (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The research article examines the development of folk theatre, with a special emphasis on the path taken by the folk-drama nautanki from its inception to the present. At first, nautanki captivated audiences with its performances, drawing sizable crowds both day and night. But as other kinds of entertainment surfaced, nautanki’s plot, length, staging, and structure changed, though its music never stopped being a highlight. The core of this folk-drama is its focus on acting, dancing, and music, which captivates audiences in both rural and urban North India. At first, nautanki told stories that were deeply ingrained in the minds of the audience historical, mythical, and modern. But in an attempt to draw in viewers, commercial pressures forced the inclusion of profanity, which destroyed the original charm. The purpose of this article is to examine two aspects of nautanki: its original splendour, which highlights its classical singing, musical instruments, and storyline, and its current form, which considers the effects of market forces, changes in the genre, and popularity.